MEMORI TRAUMA PERANG AMBON DALAM NOVEL KEI: KUTEMUKAN CINTA DI TENGAH PERANG KARYA ERNI ALADJAI - Hardianti, Sitti (Adabiyyāt: Jurnal Bahasa dan Sastra, 2022)
Kei: Kutemukan Cinta di Tengah Perang (2013) is a novel by Erni Aladjai that tells the dark events of the Ambon civil war 1999 that occurred in Ambon (Kei Islands). The problem in this research is how the author reconstructs the memory and trauma of war that caused psychic wounds for the survivors, and how this novel becomes the middle voice. The descriptive analysis method was used to look at the narrative as well as the text that gave rise to the construction of traumatic memory. Meanwhile, for the theory, Cathy Caruth's trauma memory theory is used. The results showed that all the traumatic events of the Ambon civil war that occurred in the Kei islands left psychological scars and traumatic memories for the survivors. This memory is narrated in bombings, massacres, and so on. The survivors were trauma, and the traumatic events were present in the symptoms of nightmares and flashbacks. Meanwhile, this novel can also become a middle voice to voice the other stories of the survivors in the public space. It was realizing that in fact the demands for truth and justice for them have never disappeared buried with the past.